KEANEKARAGAMAN JENIS MANGROVE DI DESA TANJUNG REJO KECAMATAN PERCUT SEI TUAN SUMATERA UTARA - Br Bangun, Julita Erischa; Kardhinata, E Harso; Susilo, Ferdinand (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2014)
Research on mangrove species diversity in the village of Tanjung Rejo Percut Sei Tuan district in North Sumatra was held in June-September 2012 which aims to determine mangrove vegetation species diversity, species density, frequency and dominance of mangrove species. Primary data obtain by sampling and direct observation by making the observation plots at the study site. Observations indicate that 14 mangrove species classified into eight families. Values of density, frequency and dominance for the highest level of the tree, and the seedling pacang contained on Avicenniaceae. Mangrove species diversity to the next level of the tree is 0.80 and the 1.38 level pacang 1.88 seedlings. The range indicates the diversity of mangrove species is low.Â